Physical Activity and Physical Activity Enjoyment in Junior High School - Eko Suhandoko; Agung Yuda Aswara; Susilo Bekti (IKIP Budi Utomo Malang, 2023)
There is strong evidence that states the fitness level of Indonesians is decreasing. Therefore, consistent physical activity is needed in everyday life. This study aims to determine whether the physical activity and physical activity enjoyment junior high school students meet the specified good criteria, whether there are differences in the physical activity and physical activity enjoyment junior high school students in Indonesia. Methods: This study used secondary data by managing the data because the data was obtained from the Center for the Study of Physical Literacy and Sports Education, IKIP Budi Utomo Malang. The population of this study is all junior high schools in Indonesia.The sample of this research was 3023 students, namely 2263 junior high school students and 760 middle school students in Indonesia.Conclusion: the physical activity of junior high school students in Indonesia does not meet the specified good criteria, the physical activity enjoyment junior high school students in Indonesia meet the specified good criteria, there is no difference in physical activity and the physical activity enjoyment junior high school students in Indonesia.